Fuda Cancer Hospital : development of private hospitals in China - Jia, Ning; Liu, Weiqi; Li, Chengwen ([London] : SAGE, 2016)
This case study, focusing on the Fuda Cancer Hospital, discusses the development of private hospitals in China.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Fuda Cancer Hospital; Hospitals -- China -- Administration -- Case studies; Medical economics -- Case studies; Hospitals -- Finance -- Case studies; Health planning -- Finance -- Case studies; Cancer -- Economic aspects -- Case studies